Optimizing the Purging Interval of 1 kW PEM Fuel Cell Control System in Fuel Cell Vehicles - Kurniawan Kurniawan; Kontan Tarigan; Andi Firdaus Sudarma; Raden Dwi Pudjisusilo; Deni Shidqi Khaerudini (Purnomo Yusgiantoro Center, 2024)
This study was conducted to explore and understand the duration of purging in fuel cell control systems and their application in fuel cell vehicles, a critical aspect that has a significant impact on the overall performance and efficiency of vehicles or devices that use fuel cell technology. The method adopted in this research involves modeling and simulation using a simulation platform, SIMULINK-MATLAB; modeling is carried out with a program and then validated with test data. This approach allows researchers to replicate and analyze system dynamics virtually to identify existing systems so that empirical models can be identified. Apart from that, the performance characteristics of the given parameters can be known by knowing the model and simulation before the physical implementation is carried out. From the study results, it was found that the modeling carried out with transfer function model 0.02635 s + 1.036/s + 0.04359 and validated with the test results 87.19% fit to estimation data was quite valid so that the model identification could be said to be suitable for this study.